Pengaruh Keterlibatan Kerja Terhadap Produktivitas Karyawan Di Favehotel Olo Padang - Amanda Ratna Dilla; Yuliana Yuliana (JURNAL PENDIDIKAN DAN KELUARGA, 2019)
This reseach aims to determine the effect of work involvement on employee productivity at Favehotel Olo Padang. This type of research is classified as associative quantitative research. The puopulationin this the reseach were all employees at Favehotel Olo Padang. The reseach sample ammounted to 38 employees with the sampling technique is saturated sampling. Data collection techniques were carried out using a questionnaire with a Likert scale that had been tested for validity ang reliability. Data were analyzed by sample linear regression testing through the help of the SPSS computer Program version 16.00. the results of the study show: 1) The involvement of employees at Favehotel Olo Padang is in poor category (39,48% ). 2) Employees productivity in the good category (42,10%). 3) R square 0.115 and a significance value of 0.037 which means that there is a significant influence between work involment on productivity is 11,5% while 88.5% is influenced by other factors.